2017
DOI: 10.1186/s13012-017-0580-1
|View full text |Cite
|
Sign up to set email alerts
|

Organizational supports used by private child and family serving agencies to facilitate evidence use: a mixed methods study protocol

Abstract: BackgroundChallenges to evidence use are well documented. Less well understood are the formal supports—e.g., technical infrastructure, inter-organizational relationships—organizations may put in place to help overcome these challenges. This study will identify supports for evidence use currently used by private child and family serving agencies delivering publicly funded behavioral health and/or human services; examine contextual, organizational, and managerial factors associated with use of such supports; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 87 publications
0
3
1
Order By: Relevance
“…Regarding macrosystem engagement, more participation in Title IV-E waiver demonstration projects by accredited agencies may signal their investment in performance improvement as reflected in COA's PQI standards. Regarding agency size, this study's finding was different from previous research that showed larger organizations with more FTEs were more likely to be accredited (Chuang, McBeath, Collins-Camargo, Lauzus, & Jolles-Perez, 2021), but it could be specific to the LADI sample. Considering COA's standards regarding service array, the finding that non-accredited agencies may collaborate to a greater extent with substance abuse treatment providers than accredited agencies was unexpected.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding macrosystem engagement, more participation in Title IV-E waiver demonstration projects by accredited agencies may signal their investment in performance improvement as reflected in COA's PQI standards. Regarding agency size, this study's finding was different from previous research that showed larger organizations with more FTEs were more likely to be accredited (Chuang, McBeath, Collins-Camargo, Lauzus, & Jolles-Perez, 2021), but it could be specific to the LADI sample. Considering COA's standards regarding service array, the finding that non-accredited agencies may collaborate to a greater extent with substance abuse treatment providers than accredited agencies was unexpected.…”
Section: Discussioncontrasting
confidence: 99%
“…COA's (2021c) standards on human resources state that organizations should assess its workforce and have a workforce development plan aligned with its strategic plan to meet current and future workforce needs. Larger private child welfare organizations, as indicated by more full-time equivalent (FTE) employees, were more likely to be accredited (Chuang, McBeath, Collins-Camargo, Lauzus, & Jolles-Perez, 2021). In a multiple case study with private child and family service organizations, undergoing COA accreditation led to hiring additional staff (Lee, 2014a).…”
Section: Organizational Capacitymentioning
confidence: 99%
“…A second U.S. study protocol in the child and family services sector described aims to examine a limited number of KT support strategies (i.e. linkages to external knowledge brokers, technology infrastructure, personnel and training and organizational strategic planning [11]; however, results have not been published. An environmental scan can generate an overview of existing organization-based EIHC and KT supports.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that HSOs where social workers generally practice lack access to or underuse different types of research, including the generic use of evidence regarding practice (Dill & Shera, 2015), the use of agency outcome data for impact evaluation and performance improvement (Kroll, 2015), and the use of research evidence in managerial decision making (Palinkas, Saldana, Chou, & Chamberlain, 2017). Other studies have found that few HSOs in prominent social work fields of practice -such as child welfare, mental health, and substance abuse treatment, including the allied health professions-use evidence-based practices despite growing demands to do so (Chuang, Collins-Camargo, & McBeath, 2017;Guerrero, He, Kim, & Aarons, 2014). Similarly, social work scholars have identified challenges to the development and support of research infrastructure pipelines within schools of social work (Guerrero, Moore & Pitt-Catsouphes, 2018), with HSOs, and with adjacent professions and institutions (for example, medical schools and hospitals) (Howard & Garland, 2015;McDermott & Bawden, 2017;Orme & Powell, 2008).…”
mentioning
confidence: 99%